Enzyme catalyzes ester bond synthesis and hydrolysis: The key step for sustainable usage of plastics - Lai, Jinghui; Huang, Huiqin; Lin, Mengwei; Xu, Youqiang; Li, Xiuting; Sun, Baoguo (Frontiers in Microbiology, 2023)
Petro-plastic wastes cause serious environmental contamination that require effective solutions. Developing alternatives to petro-plastics and exploring feasible degrading methods are two solving routes. Bio-plastics like polyhydroxyalkanoates (PHAs), polylactic acid (PLA), polycaprolactone (PCL), poly(butylene succinate) (PBS), poly(ethylene furanoate)s (PEFs) and poly(ethylene succinate) (PES) have emerged as promising alternatives. Meanwhile, biodegradation plays important roles in recycling plastics (e.g. bio-plastics PHAs, PLA, PCL, PBS, PEFs and PES and petro-plastics poly(ethylene terephthalate) (PET) and plasticizers in plastics (e.g. phthalate esters, PAEs). All these bio- and petro-materials show structure similarity by connecting monomers through ester bond. Thus, this review focused on bio-plastics and summarized the sequences and structures of the microbial enzymes catalyzing ester-bond synthesis. Most of these synthetic enzymes belonged to α/β-hydrolases with conserved serine catalytic active site and catalyzed the polymerization of monomers by forming ester bond. For enzymatic plastic degradation, enzymes about PHAs, PBS, PCL, PEFs, PES and PET were discussed, and most of the enzymes also belonged to the α/β hydrolases with a catalytic active residue serine, and nucleophilically attacked the ester bond of substrate to generate the cleavage of plastic backbone. Enzymes hydrolysis of the representative plasticizer PAEs were divided into three types (I, II and III). Type I enzymes hydrolyzed only one ester-bond of PAEs, type II enzymes catalyzed the ester-bond of mono-ester phthalates, and type III enzymes hydrolyzed di-ester bonds of PAEs. Divergences of catalytic mechanisms among these enzymes were still unclear. This review provided references for producing bio-plastics, and degrading or recycling of bio- and petro-plastics from an enzymatic point of view.